O sertão também é moderno? arquitetura moderna no Crajubar – Cariri cearense - Ribeiro, Hévila Rayara Cruz (2023)
This work aims to investigate the processes of modernization and the dissemination of modern architecture in the northeastern hinterland, taking as a spatial focus the cities of Crato, Juazeiro do Norte and Barbalha, which make up the Crajubar urban complex, in the Southern part of the state of Ceará. The choice of Crajubar as a spatial area is justified by the need for a more comprehensive view of the production of modern architecture in the northeast region of Brazil, especially in the interior cities, a topic little explored in the historiography of Brazilian architecture. Among the data collected, it was noticed that the majority of large-scale modern works were built between the 1960s and 1980s on the initiative of the State, which led to defining institutional buildings/equipment constructed with public resources during this period as research objects. As for methodological procedures, the work was divided into bibliographic review, documentary survey and mapping. The bibliographic review focused on research in books, dissertations, theses and articles related to the history and historiography of Brazilian, Northeastern and Ceará modern architecture and the formation, political, regional and economic history of Ceará state and the Cariri region. The collection and recording of data in the documentary survey was accompanied by the digitization of files (magazines, newspapers and photographs) found in institutional libraries and public and private collections. In the last stage, 22 identified modern buildings were mapped, in order to understand their insertion in the urban fabric of each of Crajubar's. Among the buildings presented are: administrative headquarters, bank branches, stadiums, bus stations, hotels, activity center, museum and public market; that marked the process of transformation of the landscape of these cities, through the use of a formal and structural composition often centered on non-local values. Finally, the research results indicate that within the movement undertaken by the State to provide the Cariri Cearense Region with a series of investments through Development Plans, in order to consolidate it as a regional hub, the cities of Crajubar were included within of the national developmental project in a simultaneous or parallel way to what was happening in the country, with the collection of modern works found in these cities being a reflection of these processes.